Z-transform in Telecommunications Systems: review and applications - Molina Ruiz, Paola Andrea; Vacca González, Harold (Ingeniería Solidaria, 2024)
Introduction: This paper explores the various applications of the Z-Transform in telecommunications, specifically in modulation, demodulation, and Dual-tone Multi-frequency (DTMF) signaling, with a focus on the Goertzel Algorithm.Problem: There is a gap in understanding the specific applications of the Z-Transform in telecommunications engineering, especially in practical systems like DTMF detection. Objective: The objective of this study is to analyze recent research on the application of the Z-Transform in telecommunications, with a particular focus on implementing Goertzel’s Algorithm in DTMF systems. Methodology: A bibliographic study was conducted to investigate the applications of the Z-Transform across various engineering fields, including control systems, automation, biomedical signal processing, and telecommunications. Additionally, a MATLAB simulation of the Goertzel Algorithm was performed and compared with the traditional Fast Fourier Transform (FFT) to evaluate its performance in detecting DTMF tones. Results: The study reveals several applications of the Z-Transform, and the simulation demonstrates that the Goertzel Algorithm is more efficient than FFT in terms of processing and detecting DTMF tones. Conclusion: The Goertzel Algorithm is identified as an efficient implementation of the Z-Transform for DTMF detection in telecommunications. It provides a viable alternative to the FFT in terms of computational efficiency, especially when dealing with a limited number of frequencies. Originality: This study combines a comprehensive literature review on the Z-Transform and Goertzel Algorithm, with a comparative analysis of their efficiency in DTMF detection, offering new insights into their practical applications. Limitations: The simulation was limited to a small set of frequencies, and further research is needed to assess the algorithm’s performance in more complex and dynamic scenarios.